Foraging ecology and occurrence of 7 sympatric babbler species (Timaliidae) in the lowland rainforest of Borneo and peninsular Malaysia. Issue 4 (14th March 2016) - Styring, Alison R.; Ragai, Roslina; Zakaria, Mohamed; Sheldon, Frederick H.
Abstract: Understanding foraging strategies of birds is essential to understanding mechanisms of their community assembly. To provide such information on a key Southeast Asian rainforest family, the babblers (Timaliidae), we evaluated foraging behavior and abundance in 7 morphologically and behaviorally similar sympatric species ( Cyanoderma erythropterum, C. rufifrons, Stachyris maculata, S. nigricollis, S. poliocephala, Macronus ptilosus, and Mixornis gularis ) in 5 habitats defined by structural complexity: (1) continuous native rainforest, (2) logged native rainforest fragments, (3) mature industrial tree plantation, (4) young industrial plantation, and (5) oil palm plantation. Enough data were obtained to compare abundance in all 7 species and foraging behavior in 5. All species were common in forest fragments and mature industrial tree plantations and less so in continuous rainforest and young industrial plantations; only M. gularis occurred in oil palm. In terms of foraging, M. gularis was the greatest generalist; C. rufifrons foraged mainly on live leaves in the forest midstory; and S. maculata, C. erythropterum, and M. ptilosus foraged mainly on dead leaves suspended in understory vegetation at significantly different heights. The dead-leaf substrate depends on a rich supply of falling leaves and extensive understory structure, conditions most common in native forest and old industrial plantations, and less so in mature forest, young plantations, and oil palm. Because of the importance of foraging data to understanding and managing biodiversity, we encourage the development of foraging fields in eBird (ebird.org), so that birdwatchers may help collect these relatively rare data.